(untitled) (Medical Forum Monthly, 2024)
Objective: This study was conducted to find out the correlation of portal vein diameter and splenic size with gastro-oesophageal varices in diagnosed cases of cirrhosis of liver. Study Design: A cross-sectional study. Place and Duration of Study: This study was conducted at the Liver Clinic, Ghulam Mohammad Mahar Medical College Hospital, Sukkur from January 2011 to December 2011. Materials and Methods: One hundred sixty four patients with cirrhosis of liver were selected for the study. Ultrasonography was performed in all cases to note the portal vein diameter and splenic size. Oesophagoa-gastr-duodenoscopy was done to detect presence of varices with grades. Results: In the study it was found that fourty patients had no varices (grade O) and the rest one hundred twenty four patients developed varices. Average portal vein diameter of patients without gastro-oesophageal varices was 11.545 ± 1.514 mm and of patients with varices 13.998 ± 1.123 mm. The difference was statistically significant (p <0.05). Average spleen size of patients without gastro-oesophageal was 13.129 ± 1.102 cm and with varices 14.997 ± 1.992 cm. This variation was also statistically significant (p < 0.05). There was a positive correlation between grading of oesophageal varices and portal vein diameter (r =0.707; p < 0.001) and between splenic size with oesophageal grades (r = 0.467; p < 0.001). Conclusion: The study portrays that with increase in portal vein diameter and splenic size, the chance of formation of gastro-oesophageal varices also increases and a positive correlation exists. Thus, measurement of portal vein diameter and splenic size by ultrasonography is a non-invasive predictive indicator of the development of gastro-oesophageal varices in cirrhosis of liver.